The Bucharest College of Physicians’ Study on Burnout Amongst Healthcare Professionals in Romania’s Capital City during COVID-19 Pandemic - Fabian KLEIN; Bogdan Ovidiu POPESCU; Lucian NEGREANU; Horia BUMBEA; Adriana MIHALAS; Catalina POIANA (Modern Medicine)
The importance of burnout amongst medical staff was highlighted by various papers, showing that this issue implies job demands and job resources. The current challenge of SARS-CoV-2 pandemic also raised many concerns about its impact on healthcare sector. A new survey after 4 years from the previous study of the Bucharest College of Physicians is coming with new data, containing the effect of COVID-19 on the psychological wellbeing of its members. The increasing of burnout was found in all categories, and the most frequently solutions claimed by the respondents were related to decreasing of workload and bureaucracy, and an important number of physicians identify the need for specialized psychological assistance. The COVID-19 pandemic period exacerbated the system related factors that contribute to the phenomenon of burnout.